The Design of a Patient Transportation Robot's Lifting Arms Considering Comfort and Safety without the Presence of a Sheet - Yong-Hoon Lee; Bok-Soo Bae; Hong Jae Yim; Yong-Kwun Lee (Journal of Robotics)
A transportation robot's lifting arms have an effect on the comfort and safety of patients. Improved arms have been designed through dynamic and static analyses to increase safety if a sheet not present on the lifting arms. To design the lifting arms, experimentation is very helpful, however, it is difficult and dangerous to experiment on patients; therefore, a simple human model was made and used for the dynamic analysis. Through the dynamic analysis results, a safe width and comfortable location for the lifting arms were determined. The thickness was then determined by static analysis and optimum design. In addition, tests have been conducted to confirm comfort and safety by deploying the designed lifting arms onto a transportation robot.